Cross-cultural validation of selected logotherapy tests among undergraduate students of University of Ibadan (2009)
The present study examined the psychometric properties and the relationships that exist among selected logo therapy tests: Logotest, Purpose in Life (PIL) test, Seeking of Noetic Goals (SONG) test, Life Purpose 'Questionnaire (LPQ), and Belfast Tests. The battery of tests was administered to 240 undergraduate students of University of Ibadan, Ibadan, Nigeria. Their ages ranged from 17 to 35 years with a mean age of 23.8 (SD = 3.1). The Cronbach Coefficient Alpha analysis showed moderate to high reliabilities. There was a positive relationship between the PIL and LPQ. Implications of the results were highlighted and recommendations for use of the tests were made.